Respostas

2013-12-01T20:08:52-02:00
A) x+y=14
    x - y=2       método da adição
    2x=16
      x=8
B)2 x - y = 4
   
-2 x +4y=6      método da adição
           3y=10
             y=10/3

C)
 x - 5  =  6 => x=11   
   2 x + y = 1     
 2 x + y = 1         método da substituição

2(11) + y=1
22 +y=1
y=21

D)
2 x - y = 1  
   2 x + 3 y = 1 .(-1) =>-2x-3y=-1          método da adição
-4y=-1.(-1)
4y=1
y=1/4

E) 
2 x + y = 4             método da substituição
    x - 2 y = 3=> x= 3 +2y
2(3+2y) +y=4
6+4y+y=4
6+5y=4
5y=-2
y=-2/5


1 5 1